Computer‐Aided Design and Synthesis of 1‐4‐[(3, 4‐Dihydroxybenzylidene)amino]phenyl‐5‐oxopyrrolidine‐3‐carboxylic Acid as an Nrf2 Enhancer. Issue 5 (8th March 2018) - Kahremany, Shirin; Babaev, Ilana; Hasin, Pinhas; Tamir, Tigist Y.; Ben‐Zur, Tali; Cohen, Guy; Jiang, Zhengyu; Weintraub, Sagiv; Offen, Daniel; Rahimipour, Shai; Major, M. Ben; Senderowitz, Hanoch; et al.
Abstract: The design and synthesis of a novel nuclear factor erythroid 2‐related factor 2 (Nrf2) enhancer is reported. Using a structure‐based virtual screening approach, several commercially available compounds were identified as having high probability to interact with the Nrf2‐binding pocket in the Kelch‐like ECH‐associated protein 1 (Keap1). Keap1 is an adaptor protein that recruits Nrf2 to a cullin‐3‐dependent ubiquitin ligase complex. The identified compounds were tested against rat pheochromocytoma PC‐12 cells for their cytoprotective activity, and one compound (SKT359126) demonstrated an Nrf2‐mediated cell‐protective effect. Based on the structure of SKT359126, 23 novel derivatives were synthesized and evaluated. Of the screened derivatives, 1‐4‐[(3, 4‐dihydroxybenzylidene)amino]phenyl‐5‐oxopyrrolidine‐3‐carboxylic acid demonstrated better activity than the parent molecules in activating the Nrf2 transduction pathway in a dose‐ and time‐dependent manner. This compound represents a promising starting point for the development of therapeutics for the treatment of oxidative‐stress‐related diseases. Abstract : Don′t stress ! A structure‐based virtual screening and lead optimization resulted in the synthesis of 1‐4‐[(3, 4‐dihydroxybenzylidene)amino]phenyl‐5‐oxopyrrolidine‐3‐carboxylic acid. The compound activated the Nrf2 transduction pathway in a dose‐ and time‐dependent manner and protected PC‐12 cells against oxidative stress. The compound can serve as a starting point for the development of therapeutics for the treatment of oxidative‐stress‐related diseases.